KEBIJAKAN PEMBERIAN REMUNERASI TERHADAP PEGAWAI PADA POLTEKKES KEMENKES BADAN LAYANAN UMUM - Suranto Suranto (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Polytechnic of the Ministry of Health since 2010 has been determined to be the agency inimplementing Financial Management General Services Agency , the Ministry of Health has setpolytechnic become Agencies Public Service Agency , the Polytechnic of the Ministry of Healthshould be managed in a sound business and in accordance with the Govermment Regulations .23 of 2005 section 35 subsection ( 1 ) Officials managers , board of supervisors , and employeesPublic Services Agency can be given remuneration based on the level of responsibility andprofessionalism required demands . Remuneration is set to the position holder is given the taskto carry out a job . In calculating the remuneration of each position needs to be preparedbeforehand Professional Grade and subsequently as a determining factor in calculating theremuneration of appraisal work ( Job Value) , so that would be obtained ranking positions ( JobGrading ) , and corporate Grade.